Impact of anti-inflammatory corticosteroids on changes in selected cytoimmunological parameters in selected interstitial lung diseases - Wędrowska, Ewelina; Pernak, Mikołaj; Wędrowski, Mateusz; Pankowska, Violetta; Waśniowski, Paweł; Piskorska, Elżbieta; Zukow, Walery (Journal of Education, Health and Sport, 2019)
Introduction. Glucocorticoids (GKS) hormones with strong immunosuppressive and anti-inflammatory activity are used, inter alia, in interstitial lung diseases (ILD). GKS inhibit excessive activity of inflammatory genes in the airways to induce apoptosis of immune cells, such as alveolar lymphocytes (AL).Objective. Assessment of cytoimmunological changes including apoptosis occurring in alveolar lymphocytes in patients with selected ILD after treatment with systemic corticosteroids.Methods. The material of the bronchoalveolar lavage (BAL) derived from patients with sarcoidosis (PS, n=66), idiopathic pulmonary fibrosis (IPF, n=27) and non-specific interstitial pneumonia (NSIP, n = 25; adequate number of patients treated with systemic GKS were 23, 8 and 6) were analyzed in cytoimmunological tests: a) percentage and the total values of BAL inflammatory cell populations; b) AL subset typing; c) CD4/CD8 index calculation; d) AL cell cycle analysis (DNA staining with propidium iodide, PI); in techniques mentioned in b) to d) items flow cytometry was used.Results. In all patient groups, treatment with GKS resulted in a decrease in the total cell number, e.g. for PS (untreated: 310 ± 80x103/ml; treated: 188 ± 43x103/ml, median ± SEM, p<0.05) and lymphocytes (untreated: 113 ± 71x103/ml; treated: 43 ± 25x103/ml median ± SEM, p<0.05). There has also been significantly lower percentage of eosinophils in all groups in GKS-treated subgroups, e.g. for IPF (untreated: 4,6 ± 3,0%, treated: 0,3 ± 0,5%), for NSIP (untreated: 1,5 ± 0,7% and treated: with 0,4 ± 0,2%; median ± SEM, p<0.05 for both). In contrast, AL apoptosis rate was significantly higher in treated patients, e.g. for PS (untreated: 0,6 ± 0,5%; treated: 4,0 ± 2,5%), NSIP (untreated: 3,4 ± 1,8%; treated: 13,1 ± 5,1%; median ± SEM, p<0.05 for both). In all GKS-treated groups corticosteroid therapy caused lower CD4/CD8 index, but only on the level of statistical tendency (e.g. for PS untreated: 4,7 ± 0,5%, treated: with 2,9 ± 0,9%) for IPF (untreated: 1,2 ± 0,5%, treated: with 1,1 ± 0,5%; median ± SEM for both).Conclusions. Systemic inflammatory glucocorticoid therapy (GKS) in all included groups of patients results in a decrease in the total number of alveolar lymphocytes, which is most likely related to the significant increase apoptosis rate of these cells. GKS medication in a similar extent caused probably both the death of helper (Th) and cytotoxic lymphocytes (Tc), since the decline in the value of CD4/CD8 index in treated patients compared with untreated ones was insignificant. A characteristic BAL cytological change in all tested ILD after GKS administration was a remarkable decrease in eosinophil percentage.